A Sequential Study of Migration and Job Search - McCall, B. P.; McCall, J. J. (Journal of Labor Economics, 1987)
"This paper designs a multiarmed bandit (MAB) sequential model for the analysis of the migration-job search process. The implications either are compatible with well-known migration behavior or, when novel, are also plausible. For example, regions with large wage variability attract migrants, and regions with large nonpecuniary returns increase both in migration and out migration. A major advantage of this approach is the relative ease with which martingale estimators can be derived from the martingale structure of the model. These martingale methods are exemplified for the return migration phenomenon."